Effect of Exercise Program on Fatigue and Depression among Geriatric Patients Undergoing Hemodialysis - Hassan Abd Elhameed, Soad; El Sayed Fadila, Doaa (International Journal of Advanced Nursing Studies, 2019)
Background: Fatigue is one of the foremost common complications faced the hemodialysis elderly patients. Fatigue notÂ onlyÂ impact the daily lives and activities of patientsÂ butÂ itÂ conjointlyÂ influences their quality of life,Â which canÂ afterwardsÂ result inÂ magnified depression, tinyÂ social interactions and increase dependency on others. Aim: Determine the effect of exercise program on fatigue and depression among geriatric patients undergoing hemodialysis. Design: Randomized controlled trial (pretest post-test) design was used. Setting: The study was carried out in the dialysis units of Mansoura University Hospital and New Mansoura General Hospital. Subjects: A purposive sample of 62 geriatric patients undergoing hemodialysis was selected and randomly allocated into two equal groups, study group (n = 31) and control group (n =31). Tools: Three tools were used; Structured interview questionnaire sheet, Multidimensional Fatigue Inventory Scale and Geriatric Depression Scale Short Form. Results: The mean age of the study and control groups was 63.45Â±4.49 and 64.7Â±5.25 respectively. A high statistically significant change in fatigue and depression score (pre and post 2 months) between the study and the control groups was observed (P=0.000). Moreover, a statistically significant relation was observed between fatigue and age of the hemodialysis geriatric patients after implementation of the exercise program (P= 0.002). Conclusion: Implementation of the exercise program proved to be effective in improving the level of fatigue and depression among geriatric patients undergoing hemodialysis in the study group. Recommendation: Encourage geriatric patients undergoing hemodialysis to perform regularly range of motion and relaxation exercises in order to alleviate fatigue and overcome depression. Â Â